Knowledge, Attitude, and Practices of Traditional Herbs and Spices Consumption among Adults in Malaysia - Khairul Ikram, Emmy Hainida; Ahmadi, Nurish Farisha; Khairul Ikram, Nur Kusaira; Muchtaridi, Muchtaridi; Muhammad, Rosmaliza (Jurnal Gizi dan Pangan, 2024)
This research aimed to assess knowledge, attitude, and practices regarding traditional herbs and spices consumption among Malaysian adults aged 18 to 60 years. A- 5-parts close-ended questionnaire was partially adapted and modified from articles and validated by 11 experts. Data collection was performed by using an online questionnaire (n=281). Most participants are female (75.4%) and Malay (85.1%), followed by Chinese (10.0%), Indian (2.1%), and other ethnicities (2.8%) such as Sabah natives, Iban, Dusun, and Javanese. Most respondents consumed traditional herbs and spices. Centella asiatica ('pegaga'), ginseng, Labisia pumila ('kacip fatimah'), and longjack ('tongkat ali') were the most consumed herbs whereas lemongrass, garlic, ginger, turmeric, and star anise were the most consumed spices. The study found good knowledge, fair attitude, and poor practice regarding traditional herbs and spices consumption. Knowledge was significantly associated with ethnicity, while consumption status was associated with attitude and practice levels. A moderate and positive correlation was observed between attitudes and practices. Enhancing public knowledge and promoting positive attitudes towards these traditional ingredients is essential for preserving cultural heritage and incorporating them into modern diets.